2022
DOI: 10.1007/s40258-022-00726-z
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness of Once-Weekly Semaglutide 1 mg versus Canagliflozin 300 mg in Patients with Type 2 Diabetes Mellitus in a Canadian Setting

Abstract: Objective Our objective was to evaluate the long-term cost-effectiveness of once-weekly semaglutide 1 mg versus once-daily canagliflozin 300 mg in patients with type 2 diabetes mellitus (T2DM) uncontrolled with metformin from the healthcare payer and societal perspectives in Canada. Methods Head-to-head data from the SUSTAIN 8 randomised trial (NCT03136484) were extrapolated over 40 years using economic simulation modelling. The cost-effectiveness of once-weekly semaglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Injectable semaglutide was found to be cost effective in all comparisons with empagliflozin [49,57,59] except one [59]. Injectable semaglutide was also found to be cost effective against canagliflozin [73]. Empagliflozin dominated liraglutide in all their comparisons [45,56,72,77].…”
Section: Glp1 Compared With Sglt2mentioning
confidence: 91%
See 4 more Smart Citations
“…Injectable semaglutide was found to be cost effective in all comparisons with empagliflozin [49,57,59] except one [59]. Injectable semaglutide was also found to be cost effective against canagliflozin [73]. Empagliflozin dominated liraglutide in all their comparisons [45,56,72,77].…”
Section: Glp1 Compared With Sglt2mentioning
confidence: 91%
“…The results of extracted data from included studies can be found in Table 1, which summarises the general characteristics of the studies. The majority of studies (n = 30) were conducted in Europe , of which many were conducted in the UK (n = 9) [37,38,40,45,46,48,51,57,62], and one-third of the studies were conducted in North America (n = 10) [64][65][66][67][68][69][70][71][72][73] and Asia (n = 8) [74][75][76][77][78][79][80][81]. Two studies were conducted outside these regions: one each from Colombia [82] and Iran [83].…”
Section: Basic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations